2014
DOI: 10.5901/mjss.2014.v5n1p325
|View full text |Cite
|
Sign up to set email alerts
|

Colour Preference among Children in a Nigerian Montessori School

Abstract: Colour preference among children has been explored in a variety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…One such mechanism may be emotional or hedonic associations, as previous research has shown that bitter taste is generally disliked or associated with danger . Additionally, black is the least favorite color of children and elicits negative emotions (Boyatzis and Varghese, 1994;Koleoso et al, 2014). Therefore, it is plausible that the association between bitter taste and black color in children is based on shared negative values .…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism may be emotional or hedonic associations, as previous research has shown that bitter taste is generally disliked or associated with danger . Additionally, black is the least favorite color of children and elicits negative emotions (Boyatzis and Varghese, 1994;Koleoso et al, 2014). Therefore, it is plausible that the association between bitter taste and black color in children is based on shared negative values .…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism may be emotional or hedonic associations, as previous research has shown that bitter taste is generally disliked or associated with danger ( Higgins and Hayes, 2019 ; Spence, 2023 ). Additionally, black is the least favorite color of children and elicits negative emotions ( Boyatzis and Varghese, 1994 ; Koleoso et al, 2014 ). Therefore, it is plausible that the association between bitter taste and black color in children is based on shared negative values ( Salgado-Montejo et al, 2015 ; Velasco et al, 2015 ; Turoman et al, 2018 ; Spence, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A landmark study [11] laid the foundation for a deep understanding of the subject. Colour perception choices are quite strong and they are dependent on a number of underlying factors such as personality types [12,6,7,8,13,14], ethnic background of the subjects [15][16][17][18], age [19][20][21][22][23][24], gender [25][26][27][28][29], education [30], mental status and information processing in such conditions [31][32][33]. It has been seen that brain activity is modulated by colour preference which implies a correlation between colour preference and personality traits; and colour preference could be a pervasive aspect of visual processing [34].…”
Section: Brief Review Of Literaturementioning
confidence: 99%